INFORMATION DISTRIBUTION AND CIRCULATION OF NETIZEN PERCEPTIONS IN THE MANDALIKA MOTOGP EVENT THROUGH THE INSTAGRAM ACCOUNT @THEMANDALIKAGP - Nurdiansyah, Dian; Anshari, Faridhian; Ciptadi, Suluh Gembyeng; Putri, Dhita Widya; Saidu, Abdulhakim (ASPIRATION Journal, 2025)
Digital communication plays a crucial role in organizing international sporting events that require extensive message dissemination and real-time audience engagement. However, the increasing volume of information distributed through social media does not necessarily produce uniform perceptions among audiences. This study aims to analyze the distribution of information and the circulation of netizen perceptions during the 2025 Mandalika MotoGP event through the Instagram account @themandalikagp.This research employs a qualitative approach using virtual observation, semi-structured interviews, and Social Network Analysis (SNA) with NodeXL and SocialBlade tools. Data validity is ensured through peer debriefing. The study involves 28 informants, consisting of followers and non-followers of the @themandalikagp account.The findings reveal that information distribution is highly centralized, following a hub-and-spoke network pattern with the official account acting as the primary information source. This structure effectively generates high audience awareness but does not result in homogeneous perceptions. Instead, netizen perceptions circulate in a heterogeneous and layered manner, forming clusters based on opinion similarity and sentiment (positive, neutral, and negative). The analysis also indicates that while network centralization facilitates rapid dissemination, it limits horizontal interaction among users.This study concludes that digital communication in social media operates beyond linear information transmission, involving dynamic processes of perception formation and meaning construction within networked environments. The novelty of this research lies in integrating information distribution, audience perception, and social network structure into a unified analytical framework. These findings contribute to the development of digital communication theory and provide practical insights for optimizing communication strategies in international sporting events.